The challenges of digital trust in Morocco between legal foundations and practical limitations - EL HOMRANI Soufyane (International Journal of Scientific Research and Innovative Studies, 2025)
The article analyzes the central role of trust in the digital economy and its legal framework in Morocco. It highlights the legislative foundations of this trust thru consumer protection, the regulation of electronic transactions, and the safeguarding of personal data. However, in the face of the rapid transformations of digital commerce, the challenges of information transparency, and the issues raised by algorithmic profiling, this framework still appears insufficient. An ambitious reform, inspired by comparative law and centered on strengthening the National Commission for Data Protection, is therefore essential to consolidate digital trust in a sustainable manner. Keywords: Digital trust - E-commerce - Transparency - Fairness - Personal data protection. Received Date: July 19, 2025 Accepted Date: August 11, 2025 Published Date: August 30, 2025 Available Online at <a style="font-size: 0.875rem;" href="https://www.ijsrisjournal.com/index.php/ojsfiles/workflow/index/435/Received%20Date:%20July%2019,%202025%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20Accepted%20Date:%20August%2011,%202025%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20Published%20Date:%20August%2030,%202025%20%20Available%20Online%20at%20https:/www.ijsrisjournal.com/index.php/ojsfiles/article/view/435">https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/435